Global environment outlook 3 : past, present and futures perspectives (London, 2002)
The contents of GEO-3 are based on information supplied by a global network of collaborating centres, and numerous individual experts and specialized institutions from around the world, giving it unrivalled accuracy and authority. Chapter 1: Integrating Environment and Development: 1972-2002 provides an overview of environment and development issues over the past 30 years. Chapter 2: State of the Environment and Policy Retrospective: 1972-2002 presents an integrated state of the environment and policy analysis of key environmental issues at global and regional levels. Chapter 3: Human Vulnerability to Environmental Change discusses increasing vulnerability of people due to environmental degradation and disasters. Chapter 4: Outlook 2002-2032 uses a scenario approach to present four different visions of the future. Chapter 5: Options for Action summarizes major cross-cutting issues and presents a range of policy actions aimed at strengthening the environmental pillar of sustainable development. The CD-ROM contains the full text of the report accompanied by a compendium of the data used in preparing it.